Beyond technology in the transition to smart campuses: the importance for policy-makers of the university community's perception. - Tomás-Miquel, José-Vicente; Capó-Vicedo, Josep; Capó-Vicedo, Jordi; Mataix Domínguez, Ainoa (Innovation: The European Journal of Social Sciences, 2023)
New challenges facing society and universities, such as the effects of climate change or the increasing levels of interconnectedness and digitisation, are changing the way we understand common spaces and teaching methods. New paradigms such as smart campuses are becoming increasingly popular in response to these new needs. This work has sought to shed light on some of the research gaps that still exist in this area of study, focusing on how the university community perceives this new model of university. Based on the information gathered from a sample of 405 members of the university community of the Alcoy Campus of the Universitat Politècnica de València in Spain, the results obtained in this research reveal a significant interest in the smart campus paradigm, albeit uneven among the different groups of university members. In addition, respondents showed a greater preference for strategies linked to the smart axes of Welfare, Environment and Education, Innovation and Research than for those based on purely technological aspects. All these findings may have relevant implications for educational research as well as for university policies and strategies.